Silica brick and preparation method thereof

By using calcium nitrate tetrahydrate and ferrous nitrate as mineralizers for silicon bricks, it provides high-active, uniformly distributed CaO and FeO, which solves the problems of low utilization rate of Fe2+ of iron mineralizer and uneven distribution of mineralizers. The production of low amorphous phase content and high-performance silicon bricks is achieved.

CN119430894AActive Publication Date: 2025-02-14INSPECTION & CERTIFICATION CO LTD MCC +1

Patent Information

Application Number
CN202510039144.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-02-14
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In the existing silicon brick production process, the Fe2+ utilization rate of iron mineralizers is low, which leads to an increase in the amorphous glass phase generation in silicon bricks, affecting the high-temperature performance of the product, and the mineralizer distribution is uneven, resulting in "iron spots". "Calcium hole" and other defects.

Method used

Calcium nitrate tetrahydrate and ferrous nitrate are used as mineralizers for silicon bricks to provide high-active and evenly distributed CaO and FeO during the firing process of silicon bricks, improving the efficiency of mineralizers and reducing the amorphous phase content.

Benefits of technology

Under the condition below the firing temperature of traditional silicon bricks, the amorphous phase content in the finished bricks is significantly reduced, the utilization efficiency of mineralizers is improved, and the high-temperature performance and product quality of silicon bricks are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of materials, and relates to a silica brick and a preparation method thereof. According to the invention, calcium nitrate tetrahydrate and ferrous nitrate are taken as mineralizing agents, CaO and FeO which are high in activity and are uniformly distributed are provided for the silica brick in the sintering process, and the problems that the mineralizing agents are difficult to uniformly disperse and Fe < 2 + > is easy to oxidize when lime milk and iron scale are taken as the mineralizing agents in the existing silica brick preparation technology, so that the utilization efficiency of the mineralizing agents is low are solved. According to the invention, mineralizer reduction and firing temperature reduction are realized by improving the use efficiency of the mineralizer, and the amorphous phase content in the finished product of the silica brick is obviously reduced on the premise of not reducing the content of phosphorus quartz. The preparation method is simple, the raw materials are rich, the cost performance is excellent, the sintering process is easy to control, the preparation method is suitable for industrial production of large silica bricks, and the finished product bricks are excellent in performance and high in percent of pass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a silicon brick and a preparation method thereof. Background Art

[0002] Silica bricks are used in large industrial furnaces such as hot blast furnaces. The production of silica bricks uses silica as the main raw material, using mineralizers to form SiO 2 The liquid phase promotes quartz (silica) to transform into phosphotquartz through the dissolution-crystallization process in the liquid phase, and finally prepares phosphotquartz as the main crystal phase, SiO 2 Silica refractory materials with a content greater than 94%. At present, the mineralizer for silica bricks used in hot blast furnaces in my country mainly adopts a combination of "lime milk + iron scale", that is, CaO-FeO-Fe 2 O 3 The mineralizers are mainly CaO and FeO (CaO-SiO 2 -FeO ternary system has the lowest eutectic point of only 1105℃). However, the firing environment of tunnel kilns for firing silica bricks in my country is mainly open oxidative conditions. Under this condition, Fe 2+ Inevitably, Fe 3+ This greatly reduces the efficiency of iron mineralizers (as Fe 2+ / Fe 3+ The ratio of FeO-Fe 2 O 3 -SiO 2 The lowest eutectic point of the ternary system will rise to a maximum of 1455°C). This results in the current production process of silica bricks, despite the use of iron mineralizers, the firing temperature is still as high as 1450°C-1470°C.

[0003] At the same time, SiO in silicon bricks 2 The content is also very important, high SiO 2 The content is the guarantee of long service life of silica bricks. At present, the silica brick product standard requires that the SiO content of silica bricks 2 The content must reach more than 94%. This leads to another problem in the current silica brick production process using iron mineralizers: Fe 2+ The low utilization rate leads to an increase in the amount of iron mineralizer introduced into silica bricks, and then an increase in the amount of amorphous glass phase generated in the finished bricks (the amorphous phase content in domestic silica bricks is generally above 15%). As a low-melting phase, the amorphous phase is first not conducive to the high-temperature performance of the product. Most silica bricks are damaged during use due to high-temperature creep caused by the low-melting phase. At the same time, SiO 2 The SiO2 content of the entire product will be calculated when the product chemical composition is tested. 2Therefore, improving the utilization efficiency of iron mineralizers in silica bricks and reducing the amorphous phase content in finished bricks are very important for optimizing the silica brick production process and improving the performance of silica bricks.

[0004] For silica bricks, another important factor is the uniformity of mineralizer distribution in the bricks. Uneven distribution of mineralizers will form defects such as "iron spots" and "calcium holes" in fired bricks, and cracks in the brick body due to uneven thermal expansion, which is the main reason for the high scrap rate in silica brick production. When using the traditional combination of lime milk and iron scale mineralizer, there are problems such as trace amounts of iron scale fine powder being difficult to disperse evenly in the silica bricks, and the lime milk solution being easy to flocculate and difficult to disperse. Summary of the invention

[0005] In order to solve the above defects in the prior art, the present invention provides a silica brick and a preparation method thereof.

[0006] In the present invention, calcium nitrate tetrahydrate and ferrous nitrate are introduced as silica brick mineralizers to provide highly active and evenly distributed CaO and FeO during the silica brick sintering process, thus solving the problems of uneven distribution of traditional silica brick mineralizers and Fe 2+ The problem of difficult to stabilize existence has overall improved the utilization efficiency of mineralizers, reduced the amount of mineralizer added, and ultimately achieved the production of high-quality silica bricks with low amorphous phase content at a temperature lower than the firing temperature of traditional silica bricks.

[0007] The technical solution adopted by the present invention is as follows:

[0008] A silica brick, wherein the raw material of the silica brick comprises a mineralizer, the mineralizer comprises calcium nitrate tetrahydrate and ferrous nitrate, and the mass ratio of calcium nitrate tetrahydrate to ferrous nitrate is 4-12:1, preferably 6-12:1.

[0009] After the raw materials containing mineralizers of the present invention are made into bricks, they are heated up and sintered under reducing atmosphere conditions (the target temperature of the heating is preferably 1300-1400°C), which can introduce highly active and evenly distributed CaO and FeO, solving the problems of uneven distribution of mineralizers and FeO in traditional silicon bricks. 2+ The problem of difficult to stabilize existence has improved the overall efficiency of mineralizer use.

[0010] Preferably, based on the total amount of raw materials of the silicon brick, the mass content of calcium nitrate tetrahydrate is 0.1%-8%, preferably 1%-8%, and further preferably 1%-7%, and the mass content of ferrous nitrate is 0.1%-2%, preferably 0.5%-2%.

[0011] More preferably, the total amount of calcium nitrate tetrahydrate and ferrous nitrate is 2%-10% of the total amount of the silica brick raw materials, which is more conducive to the transformation of quartz to tridymite during the firing process of silica bricks.

[0012] Preferably, the raw materials of the silicon bricks further include silica and waste silicon bricks. Based on the total amount of raw materials of the silicon bricks, the mass content of silica is 60%-98.8%, and the mass content of the waste silicon bricks is 1%-30%, preferably 5%-20%.

[0013] Preferably, the silica comprises a first silica aggregate with a particle size of ≤ 2.5 mm and > 0.5 mm, a second silica aggregate with a particle size of ≤ 0.5 mm, and silica fine powder with a particle size of ≤ 200 mesh; and the particle size of the waste silica bricks is ≤ 0.5 mm.

[0014] Further preferably, based on the total amount of raw materials of the silica brick, the silica includes 10%-40% of the first silica aggregate, 30%-70% of the second silica aggregate, and 15%-45% of silica fine powder.

[0015] More preferably, based on the total amount of raw materials of the silica brick, the silica includes 15%-35% of the first silica aggregate, 30%-45% of the second silica aggregate, and 15%-18.8% of silica fine powder.

[0016] Preferably, the raw materials of the silicon bricks also include a binder, and the amount of the binder is 0.5%-3% of the total amount of the silicon brick raw materials. Using an appropriate amount of binder, combined with silica fine powder, ferrous nitrate and calcium nitrate tetrahydrate, can make the bricks have higher strength after forming and drying, which is more conducive to the stacking work in the firing process.

[0017] Preferably, the binder is a mixture of one or more of yellow dextrin, white dextrin and pulp dry powder.

[0018] In the present invention, the waste silica bricks are obtained by crushing the remaining silica bricks produced.

[0019] Preferably, the mineralizer does not contain iron scale.

[0020] The content of amorphous phase in the silica brick of the present invention is below 8 wt%, and the content of phosphotquartz is 60-80 wt%. The present invention reduces the amount of mineralizer and lowers the firing temperature by improving the use efficiency of the mineralizer, and the silica brick produced significantly reduces the content of amorphous phase in the finished brick without reducing the content of phosphotquartz.

[0021] The present invention uses calcium nitrate tetrahydrate and ferrous nitrate as mineralizers to provide highly active and evenly distributed CaO and FeO during the firing process of silica bricks, thereby solving the problems of the mineralizer being difficult to evenly disperse and FeO being difficult to disperse when "lime milk + iron scale" is used as the mineralizer in the existing silica brick preparation technology. 2+The problem of low utilization efficiency of mineralizers due to easy oxidation. The present invention reduces the amount of mineralizers and lowers the firing temperature by improving the utilization efficiency of the mineralizers. The produced silica bricks significantly reduce the amorphous phase content in the finished bricks without reducing the content of phosphotarzite. The preparation method of the present invention is simple, the raw materials are abundant and cost-effective, the firing process is easy to control, and it is suitable for the industrial production of large-scale silica bricks. The finished bricks have excellent performance and a high pass rate.

[0022] The present invention also provides a method for preparing the silica brick, comprising the following steps:

[0023] S1, mixing and stirring raw materials including a mineralizer to prepare a mixed mud;

[0024] S2, using a press to press the mixed mud in S1 into a brick, after drying, heating to 1300-1400°C under a reducing atmosphere for sintering to obtain a finished product. The present invention can sinter to form silica bricks at low temperatures. Ferrous nitrate will not be oxidized to trivalent iron under a reducing atmosphere, and will not affect the effect of using calcium nitrate tetrahydrate and ferrous nitrate as silica brick mineralizers.

[0025] Preferably, the mixing and stirring of the raw materials including the mineralizer in S1 specifically includes:

[0026] S101, weigh silica fine powder, calcium nitrate tetrahydrate, and ferrous nitrate according to a ratio, mix them at 55° C.-65° C., then add a binder and stir evenly to form a mud material;

[0027] S102, weigh the first silica aggregate, the second silica aggregate, and the waste silica bricks according to a proportion, and mix them evenly with the mud in S101.

[0028] Preferably, the drying process in S2 includes: drying at less than 200° C. for 24-48 hours, which is more conducive to the hardening of the binder.

[0029] Preferably, the sintering time in S2 is 6-30 hours, which is more conducive to the full conversion of quartz into tridymite in the silicon brick.

[0030] In the present invention, calcium nitrate tetrahydrate and ferrous nitrate are used as mineralizers for silica bricks, and the mineralizers are evenly distributed in the bricks by liquid phase mixing at 55°C-65°C. Then, heat treatment is performed under reducing atmosphere conditions (such as the presence of hydrogen and / or carbon monoxide) to form uniformly distributed highly active CaO and FeO in the bricks (reactions 1-4). After the firing temperature is raised to 1105°C, the CaO and FeO introduced by the mineralizer first form CaO-SiO in the silica bricks together with the silica fine powder. 2 -FeO ternary liquid phase, and then the quartz phase in the silicon brick continues to change from CaO-SiO 2-FeO dissolves in the ternary liquid phase, crystallizes and transforms into phosphotquartz, ultimately achieving the firing of high-performance silica bricks at a lower temperature.

[0031] Ca(NO 3 ) 2 ·4H 2 O→Ca(NO 3 ) 2 (1)

[0032] Ca(NO 3 ) 2 →Ca(NO 2 ) 2 (2)

[0033] Ca(NO 2 ) 2 →CaO (3)

[0034] 2Fe(NO 3 ) 2 =2FeO+4NO 2 +O 2 (4)

[0035] Beneficial effects:

[0036] In view of the shortcomings and defects of the current use of "iron scale + lime milk" as a mineralizer to produce silica bricks, the present invention selects a mineralizer containing calcium nitrate tetrahydrate and ferrous nitrate to prepare silica bricks, which produces the following beneficial effects:

[0037] (1) The melting point of calcium nitrate tetrahydrate is 45℃, and the melting point of ferrous nitrate is 60.5℃. Their melting points are close. During the mixing process, calcium nitrate tetrahydrate and ferrous nitrate are transformed into liquid phase, which can achieve their uniform distribution in the silica brick; and due to their decomposition reaction at high temperature, highly active CaO and FeO can be introduced. The effective substances CaO and FeO in the mineralizer are all obtained through reaction decomposition. Compared with directly adding CaO and FeO raw materials, the decomposition substances are more active; at the same time, the reducing atmosphere conditions in the shuttle kiln protect Fe 2+ The highly active CaO and FeO evenly distributed in the silica bricks can significantly improve the utilization efficiency of the mineralizer. The mass ratio of calcium nitrate tetrahydrate and ferrous nitrate is controlled within an appropriate range, which can increase the amount of liquid phase generated and promote the transformation of quartz to tridymite. Traditional mineralizers use trivalent iron (such as ferric nitrate), so the utilization efficiency of the mineralizer is low.

[0038] (2) Improving the utilization efficiency of mineralizers can reduce the amount of silica brick mineralizers and the sintering temperature of silica bricks, thereby achieving the sintering of high-quality silica bricks with low amorphous phase content at a sintering temperature lower than that of traditional silica bricks; in the present invention, different crystalline phases are measured by mass.

[0039] (3) The silica bricks of the present invention have high strength, good high-temperature volume stability, high-temperature thermal shock resistance and excellent high-temperature creep performance;

[0040] (4) The preparation method of the present invention is simple, the raw materials are abundant and cost-effective, the firing process is easy to control, and it is suitable for the industrial production of large-scale silica bricks with a high pass rate. DETAILED DESCRIPTION

[0041] The same raw materials in the following embodiments have the same particle size, specifically: a first silica aggregate with a particle size of ≤ 2.5 mm and > 0.5 mm, a second silica aggregate with a particle size of ≤ 0.5 mm, and silica fine powder with a particle size of ≤ 200 mesh; the particle size of the waste silica bricks is ≤ 0.5 mm.

[0042] Example 1

[0043] First, 15 wt% of silica fine powder, 1 wt% of ferrous nitrate and 6 wt% of calcium nitrate tetrahydrate are mixed at 62°C, and 1.5 wt% of pulp dry powder binder is added to the above mixture, and the mixture is evenly mixed to form a mud material; then 30 wt% of the first silica aggregate, 38 wt% of the second silica aggregate, and 10 wt% of waste silica bricks are evenly mixed with the mud material and pressed into shape; after drying, the mixture is placed in a shuttle kiln and fired at 1350°C for 30 hours under reducing atmosphere conditions (carbon monoxide atmosphere) to obtain silica bricks.

[0044] The obtained silica brick was tested and found to have an apparent porosity of 18.0% and a bulk density of 1.89 g / cm 3 The room temperature compressive strength is 58.3 MPa, the load softening temperature is 1671℃, the tridymite content is 70 wt%, the cristobalite content is 24%, and the glass phase content is 3%. The product qualification rate is 93%.

[0045] Example 2

[0046] First, 15 wt% of silica fine powder, 2 wt% of ferrous nitrate and 8 wt% of calcium nitrate tetrahydrate are mixed at 62°C, and 1 wt% of yellow dextrin binder is added to the above mixture, and the mixture is evenly mixed to form a mud material; then 30 wt% of the first silica aggregate, 40 wt% of the second silica aggregate, and 5 wt% of waste silica bricks are evenly mixed with the mud material and pressed into shape; after drying, the mud material is placed in a shuttle kiln and sintered at 1300°C for 24 h in a carbon monoxide atmosphere to obtain a silica brick.

[0047] The obtained silica brick was tested and found to have an apparent porosity of 18.5% and a bulk density of 1.86 g / cm 3 The room temperature compressive strength is 54.3 MPa, the load softening temperature is 1665℃, the tridymite content is 71 wt%, the cristobalite content is 21%, and the glass phase content is 5%. The product qualification rate is 95%.

[0048] Example 3

[0049] First, 15 wt% of silica fine powder, 0.5 wt% of ferrous nitrate and 4 wt% of calcium nitrate tetrahydrate are mixed at 62°C, and 2 wt% of yellow dextrin binder is added to the above mixture, and the mixture is evenly mixed to form a mud material; then 30 wt% of the first silica aggregate, 44 wt% of the second silica aggregate, and 6.5 wt% of waste silica bricks are evenly mixed with the mud material and pressed into shape; after drying, the mud material is placed in a shuttle kiln and sintered at 1400°C for 24 h in a carbon monoxide atmosphere to obtain a silica brick.

[0050] The obtained silica brick was tested and found to have an apparent porosity of 17.8% and a bulk density of 1.90 g / cm 3 The room temperature compressive strength is 55.1 MPa, the load softening temperature is 1675℃, the tridymite content is 65 wt%, the cristobalite content is 31%, and the glass phase content is 2%. The product qualification rate is 89%.

[0051] Example 4

[0052] First, 15 wt% of silica fine powder, 0.5 wt% of ferrous nitrate and 6 wt% of calcium nitrate tetrahydrate are mixed at 62°C, and 3 wt% of white dextrin binder is added to the above mixture, and the mixture is evenly mixed to form a mud material; then 30 wt% of the first silica aggregate, 36.5 wt% of the second silica aggregate, and 12 wt% of waste silica bricks are evenly mixed with the mud material and pressed into shape; after drying, the mixture is placed in a shuttle kiln and fired at 1400°C for 30 hours in a carbon monoxide atmosphere to obtain silica bricks.

[0053] The obtained silica brick was tested and found to have an apparent porosity of 17.9% and a bulk density of 1.89 g / cm 3 The room temperature compressive strength is 57.3 MPa, the load softening temperature is 1677℃, the tridymite content is 67 wt%, the cristobalite content is 28%, and the glass phase content is 2%. The product qualification rate is 90%.

[0054] Example 5

[0055] The method of Example 1 is referred to, except that the amount of calcium nitrate tetrahydrate is 6 wt% unchanged, and the amount of ferrous nitrate is adjusted so that the mass ratio of calcium nitrate tetrahydrate to ferrous nitrate is 4: 1. For this purpose, the amount of waste silica bricks is adaptively adjusted so that the total amount of silica fine powder, ferrous nitrate and calcium nitrate tetrahydrate, the first silica aggregate, the second silica aggregate, and the waste silica bricks is 100%.

[0056] The obtained silica brick was tested and found to have an apparent porosity of 17.9% and a bulk density of 1.89 g / cm 3The room temperature compressive strength is 54.6 MPa, the load softening temperature is 1670℃, the tridymite content is 67 wt%, the cristobalite content is 27%, and the glass phase content is 3%. The product qualification rate is 95%.

[0057] Comparative Example 1

[0058] The method of Example 1 is referred to, except that ferrous nitrate is not added. For this purpose, the amount of waste silica bricks is adaptively adjusted so that the total amount of silica fine powder, calcium nitrate tetrahydrate, the first silica aggregate, the second silica aggregate, and the waste silica bricks is 100%.

[0059] The obtained silica brick was tested and found to have an apparent porosity of 18.5% and a bulk density of 1.87 g / cm 3 The room temperature compressive strength is 50.9 MPa, the load softening temperature is 1670℃, the tridymite content is 61 wt%, the cristobalite content is 25%, and the glass phase content is 3%. The product qualification rate is 81%.

[0060] Compared with Example 1, Comparative Example 1 does not add ferrous nitrate, which leads to a change in the composition of the mineralizer, a poor mineralization effect, a significant decrease in the content of tridymite, and a significant decrease in the qualified rate of the product; the amount of liquid phase formed by the mineralizer at high temperature is reduced, and the porosity after firing is slightly increased, the bulk density is slightly decreased, and the compressive strength is slightly decreased.

[0061] Comparative Example 2

[0062] The method of Example 1 is referred to, except that calcium nitrate tetrahydrate is replaced by lime milk, and the mass ratio of ferrous nitrate to lime milk is 1: 2. For this purpose, the amount of waste silica bricks is adaptively adjusted so that the total amount of silica fine powder, ferrous nitrate and lime milk, the first silica aggregate, the second silica aggregate, and the waste silica bricks is 100%.

[0063] The obtained silica brick was tested and found to have an apparent porosity of 18.2% and a bulk density of 1.87 g / cm 3 The room temperature compressive strength is 47.3 MPa, the load softening temperature is 1668℃, the tridymite content is 63 wt%, the cristobalite content is 30%, and the glass phase content is 4%. The product qualification rate is 83%.

[0064] Compared with Example 1, Comparative Example 2 uses lime milk instead of calcium nitrate tetrahydrate, which results in poor mixing uniformity of the mineralizer, significantly reduced strength, slightly reduced tridymite content, and significantly reduced product qualification rate.

[0065] Comparative Example 3

[0066] The method of Example 1 is referred to, except that the amount of ferrous nitrate is adjusted so that the mass ratio of calcium nitrate tetrahydrate to ferrous nitrate is 2: 1. For this purpose, the amount of waste silica bricks is adaptively adjusted so that the total amount of silica fine powder, ferrous nitrate and calcium nitrate tetrahydrate, the first silica aggregate, the second silica aggregate, and the waste silica bricks is 100%.

[0067] The obtained silica brick was tested and found to have an apparent porosity of 18.0% and a bulk density of 1.88 g / cm 3 The room temperature compressive strength is 51.5 MPa, the load softening temperature is 1643℃, the tridymite content is 70 wt%, the cristobalite content is 21%, and the glass phase content is 8%. The product qualification rate is 95%.

[0068] Compared with Example 1, the total amount of mineralizer in Comparative Example 3 is increased, and the content of ferrous nitrate is too large, resulting in excessive liquid phase, which leads to a significant decrease in the load softening temperature; excessive introduction of iron elements leads to a significant increase in the glass phase content.

[0069] Comparative Example 4

[0070] The method of Example 1 is followed, except that the dried bricks are fired in an air atmosphere in a tunnel kiln at a firing temperature of 1460° C. for 30 hours.

[0071] The obtained silica brick was tested and found to have an apparent porosity of 18.0% and a bulk density of 1.88 g / cm 3 The room temperature compressive strength is 56.5 MPa, the load softening temperature is 1668℃, the tridymite content is 65 wt%, the cristobalite content is 20%, and the glass phase content is 17%. The product qualification rate is 86%.

[0072] Compared with Example 1, Fe 2+ Oxidized Fe 3+ , the mineralization effect of the mineralizer becomes worse, and the tridymite content decreases; the liquid phase formation temperature increases, and the product qualification rate decreases (the liquid phase can relieve stress); Fe 3+ It is easier to form a glass phase, and the glass phase content is significantly increased.

[0073] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A silica brick, wherein the raw material of the silica brick includes a mineralizer, characterized in that: The mineralizer comprises calcium nitrate tetrahydrate and ferrous nitrate, and the mass ratio of calcium nitrate tetrahydrate to ferrous nitrate is 4-12:

1.

2. The silica brick according to claim 1, characterized in that: Based on the total amount of raw materials of silica bricks, the mass content of calcium nitrate tetrahydrate is 0.1%-8%, and the mass content of ferrous nitrate is 0.1%-2%.

3. The silica brick according to claim 1 or 2, characterized in that: The total amount of calcium nitrate tetrahydrate and ferrous nitrate is 2%-10% of the total amount of silica brick raw materials.

4. The silica brick according to claim 1 or 2, characterized in that: The raw materials of the silicon bricks also include silica and waste silicon bricks. Based on the total amount of raw materials of the silicon bricks, the mass content of silica is 60%-98.8%, and the mass content of the waste silicon bricks is 1%-30%.

5. The silica brick according to claim 4, characterized in that: The silica includes a first silica aggregate with a particle size of ≤ 2.5 mm and > 0.5 mm, a second silica aggregate with a particle size of ≤ 0.5 mm, and silica fine powder with a particle size of ≤ 200 mesh; the particle size of the waste silica bricks is ≤ 0.5 mm; and based on the total amount of raw materials of the silica bricks, the silica includes 10%-40% of the first silica aggregate, 30%-70% of the second silica aggregate, and 15%-45% of the silica fine powder.

6. The silica brick according to claim 5, characterized in that: The raw materials of the silica bricks also include a binder, the amount of which is 0.5%-3% of the total amount of the silica brick raw materials, and the binder is a mixture of one or more of yellow dextrin, white dextrin, and pulp dry powder.

7. The silica brick according to claim 1, characterized in that: The mineralizer does not contain iron scale; And / or, the amorphous phase content in the silica brick is below 8 wt%, and the phosphorus quartz content is 60-80 wt%.

8. A method for preparing a silica brick as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: S1, mixing and stirring raw materials including a mineralizer to prepare a mixed mud; S2. The mixed mud in S1 is pressed into a brick by a press, and after drying, the mixture is heated to 1300-1400° C. in a reducing atmosphere for sintering to obtain a finished product.

9. The method for preparing silica bricks according to claim 8, characterized in that: The raw materials including the mineralizer are mixed and stirred as described in S1, specifically including: S101, weigh silica fine powder, calcium nitrate tetrahydrate, and ferrous nitrate according to a ratio, mix them at 55° C.-65° C., then add a binder and stir evenly to form a mud material; S102, weigh the first silica aggregate, the second silica aggregate, and the waste silica bricks according to a proportion, and mix them evenly with the mud in S101.

10. The preparation method according to claim 8, characterized in that: The drying process in S2 includes: drying at less than 200° C. for 24-48 hours; and / or, the sintering time in S2 is 6-30 hours.

Citation Information

Patent Citations

  • Silica brick and preparation method thereof

    CN102167606A

  • Silica brick added with calcium nitrate tetrahydrate and preparation method thereof

    CN115536409A

  • Preparation method of light-weight silica brick and light-weight silica brick prepared by preparation method

    CN117142877A

  • manufacturing process of refractory silica

    FR1107559A

Cited By

  • High-precision preparation method of siliceous refractory brick for glass kiln

    CN121824139A

  • High-precision preparation method of siliceous refractory bricks for glass kiln

    CN121824139B